The Relevance of Progressivism's Educational Philosophy in the Implementation of the Independent Curriculum: A Critical Analysis - Tetty Siska; Hasnah Faizah (International Forum of Researchers and Lecturers, 2025)
The Merdeka Curriculum policy, initiated by the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek), marks a significant paradigm shift in the Indonesian educational landscape. This curriculum emphasizes student-centered learning, flexibility, and the development of competencies according to students' interests and talents. This study aims to critically analyze the relevance of the philosophy of progressivism, pioneered by John Dewey, as a conceptual foundation for the implementation of the Merdeka Curriculum. Using a systematic literature review method on 15 Sinta indexed scientific journals (minimum Sinta 4) published between 2018-2024, this study examines the alignment between the core principles of progressivism such as experience as the basis of learning (learning by doing), the teacher's role as a facilitator, problem-solving, and democratic education and the essence of the Merdeka Curriculum policy. The analysis reveals a strong alignment between the two concepts. Project-based learning, content differentiation, and formative assessment within the Merdeka Curriculum are concrete manifestations of progressive ideas. However, this study also identifies implementation challenges, such as teacher readiness, school culture transformation, and resource availability, which can hinder the internalization of this philosophy at the practical level. It is concluded that a deep understanding of the philosophy of progressivism by stakeholders, especially educational managers and teachers, is crucial to ensure that the Merdeka Curriculum becomes not just an administrative change, but also a substantive and sustainable pedagogical transformation.